Improving a gamified m-learning application based on the continuance usage intention influencing factors - Roslan, Rosfuzah; Mohd Ayub, Ahmad Fauzi; Ghazali, Norliza (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
The inclusion of gamification technology can have a positive effect on the development of innovative mobile-learning (m-learning) application. It is difficult to maintain the students’ retention in a m-learning tool, hence measures should be taken by the developers and researchers to keep the users interested in the tool. This study aims to utilise the knowledge gathered from a correlational survey research involving 140 first year Diploma of Information Technology respondents, to find the influencing factors of continuance usage intention towards a gamified e-quiz mobile application among Malaysian Higher Education students. Based on the result of the influencing factors; (i) perceived ease of use, (ii) perceived usefulness, (iii) social influence and (iv) perceived enjoyment, gamification items in the m-learning tool are linked with the constructs. Pearson Correlation Analysis showed that there is a positive relationship between perceived ease of use (rs =.593** p > 0.05), perceived usefulness (rs =.694** p > 0.05), social influence (rs =.720** p > 0.05) and perceived enjoyment (rs =.700**p > 0.05) with continuance usage intention. Further analysis using multiple regression shows that social influence and perceived enjoyment, influence the continuance usage intention among the students with a contribution of 35.1% (β = .351) and 31.9% (β = .319), respectively. Tool Improvement Plan (TIP) document can be produced based on the corresponding influential factors. This way, the m-learning tool developers can make wise judgement on important tool upgrades.